Health systems' capacity to provide post-abortion care: a multicountry analysis using signal functions. Issue 1 (January 2019) - Owolabi, Onikepe O; Biddlecom, Ann; Whitehead, Hannah S
Summary: Background: Abortion-related mortality is one of the main causes of maternal mortality worldwide. Laws often restrict the provision of safe abortion care, yet post-abortion care is a service that all countries have committed to provide to manage abortion complications. There is minimal evidence on the capacity of national health systems to provide post-abortion care. Methods: We did a multicountry analysis of data from nationally representative Service Provision Assessment surveys done between 2007 to 2017 in ten countries across three regions (Bangladesh, Haiti, Kenya, Malawi, Namibia, Nepal, Rwanda, Senegal, Tanzania, and Uganda). Data were available for all ten countries from 2007 to 2015. We included facilities offering childbirth delivery services and classified facilities as primary or referral level. We measured signal functions for post-abortion care (the availability of key equipment and ability to perform services) to assess the proportion of primary-level and referral-level facilities in each country with the capacity to provide basic and comprehensive post-abortion care, respectively. We calculated the proportion of facilities providing each post-abortion care signal function to examine specific gaps in service provision. Findings: There are critical gaps in the provision of post-abortion care at all facilities that offer delivery services. In seven (70%) of ten countries, less than 10% of primary-level facilities could provide basic post-abortion care, and in eight (80%) of ten countries less than 40% of referral-level facilities could provide comprehensive post-abortion care. In no country could all referral facilities provide all the essential services that need to be included in basic post-abortion care. Interpretation: The capacity of primary-level and referral-level health facilities to provide basic and comprehensive post-abortion care, respectively, is low. The results highlight the gap between political commitments to address the consequences of unsafe abortion and the capacity of health systems to provide post-abortion care. Increasing the provision of good-quality post-abortion care is essential to reduce the level of abortion-related morbidity and mortality. Funding: UK Aid from the UK Government.